Co-created research agenda to support advocacy toward social inclusion for sexual and gender minorities in sub-Saharan Africa. Issue 3 (3rd July 2022) - Igonya, Emmy Kageha; Ajayi, Anthony I.; Otukpa, Emmanuel; Juma, Kenneth; Ouedraogo, Ramatou; Kibunja, Grace; Mwoka, Meggie; Opondo, Winnie; Kabiru, Caroline W.; Ushie, Boniface Ayanbekongshie
Abstract: Advocacy actors play a unique role in promoting changes in policy, legal, and social environments for sexual and gender minorities in sub-Saharan Africa (SSA). However, their efforts may be hampered by limited incorporation of evidence because there is a massive gulf between what researchers focus on and what evidence users need. Together with fifty key stakeholders across SSA, we—a team of researchers and policy engagement specialists—co-created a research agenda and identified policy goals and research priorities to support evidence-informed policy and advocacy that can foster social inclusion of sexual and gender minorities in the region. We identified six research priority areas: (1) The history of lesbian, gay, bisexual and trans people and people whose identities do not conform to typical binary notions of male and female, or identify themselves using other categories to describe sexuality (LGBT+) in Africa and their lived realities; (2) Cost of non-inclusion and benefits of inclusion; (3) Strategies fostering inclusion; (4) Challenges and needs of LGBT + people; and (5) Implementation science on the effectiveness of provisions in sexual and reproductive health and HIV strategies or guidelines; and (6) Understanding the existing policy and legal architecture. This co-created research agenda can guide the generation of policy-relevant evidence, increase collaboration between researchers and policy actors, and increase research uptake to support efforts toward inclusion.